Dry Eye Pasca Operasi Katarak yang diberikan Diquafosol Sodium - Natasya Jasmine Azzahra; Muhammad Maulana (Medula, 2026)
Dry eye is one of the most common complications following cataract surgery, primarily caused by tear film instability, ocular surface epithelial damage, and altered mucin secretion. This condition may reduce visual comfort, delay postoperative recovery, and negatively impact patients’ quality of life. Recent literature from the last five years indicates that 3% Diquafosol sodium, a P2Y₂ receptor agonist, provides substantial therapeutic benefits by promoting tear and mucin secretion, enhancing ocular surface integrity, and supporting epithelial repair after surgical trauma. Multiple studies report that Diquafosol, either as monotherapy or in combination with sodium hyaluronate, significantly improves tear breakup time (TBUT), reduces corneal and conjunctival staining, and enhances Schirmer test scores. Improvements in subjective symptoms, including dryness, irritation, and discomfort, were also noted in many postoperative individuals. Perioperative administration initiated prior to surgery and continued during the healing phase has demonstrated superior outcomes compared to postoperative use alone. However, heterogeneity among study designs, variation in treatment duration, and inconsistent subjective symptom improvement remain limitations in current evidence. Overall, available scientific findings support Diquafosol sodium as an effective and safe therapeutic option for managing postoperative dry eye and suggest its incorporation into standard management protocols, especially for patients with pre-existing dry eye or those at high risk.